Influence of Financial Technology Usage, Consumer Protection, and Financial Literacy on Financial Inclusion - Cristia Cristia; Juniati Gunawan; Angelica Valerie Amaranydia (Citakonsultindo, 2024)
Financial inclusion is essential for the economic development and stability of a society, particularly in developing regions. The rapid advancement of financial technology (fintech), coupled with the necessity for consumer protection and enhanced financial literacy, plays a crucial role in promoting financial inclusion. This research aims to examine the factors influencing financial inclusion, focusing on the use of financial technology, consumer protection, and financial literacy among women aged 17-27 residing in Jakarta who have been using financial technology for at least one year. Data were collected via online questionnaires, resulting in responses 208 participants. The research employs a quantitative approach using method Partial Least Squares Structural Equation Modeling (PLS-SEM) and using Smart PLS 3 software for data analysis. The findings indicate that the use of financial technology, consumer protection, and financial literacy each have a significant positive impact on financial inclusion. The results support the hypothesis that these factors are critical in enhancing financial inclusion.